Acute Airway Obstruction and Cardiopulmonary Arrest due to Tracheomalacia Caused by Megaesophagus Compression Secondary to Achalasia. (9th May 2020) - Aubignat, Mickael; Roger, Pierre-Alexandre; Dernoncourt, Amandine; Salle, Valery; Smail, Amar; Gourguechon, Clement; Schmidt, Jean; Duhaut, Pierre
Abstract : We report the case of an 80-year-old woman who presented one episode of cardiopulmonary arrest and two episodes of acute airway obstruction. We found in this patient the presence of tracheomalacia caused by megaesophagus compression secondary to achalasia probably responsible for episodes of acute airway obstruction and cardiopulmonary arrest.